CROSSING THE GOSPEL OF GOD'S KINGDOM AMIDS THE STORM OF COVID-19 - Haans, Albert Leonarts Jantje (International Journal of Social and Management Studies, 2021)
God's greatest mission is to save lost sinners from the throne of God's grace, the church, and His people should take action to be responsible for carrying out the great commandment, namely preaching the gospel Amid the Covid 19 storm. Qualitative research, namely using descriptive methods that can give a comprehensive overview of various important information collected through literature books, theological journals, and practical things that Christians can do. Amid these very difficult conditions, where the mobility of human movement is very limited, encounters between humans are very rare, the communication strategy for preaching the gospel must continue by utilizing various creativity in the form of social media, digital media, internet, gadgets, and practical things. Limited under the power and control of the Holy Spirit is expected to be a fairly effective means of proclaiming the Gospel. Cell group activities in implementing the preaching of the gospel consistently and regularly, so that the spread of the gospel of the Kingdom of God can still take place by utilizing the right and biblical strategies.